Sleep Patterns in Pregnant Women with Obesity Differentially Affect Energy Intake and Metabolic Health. (29th May 2020) - Flanagan, Emily; Altazan, Abby; Most, Jasper; Beyl, Robbie; Hsia, Daniel; Amant, Marshall St; Singh, Prachi; Redman, Leanne
Abstract: Objectives: During pregnancy, altered glucose kinetics coupled with disrupted sleep increase the risk for adverse metabolic health outcomes. The aim of this prospective, observational study in pregnant women with obesity was to 1) examine sleep patterns in early and late pregnancy; and 2) identify how changes in sleep patterns impact gestational weight gain, energy intake and metabolic health. Methods: In 52 healthy pregnant women with obesity (27.4 ± 0.6 y; BMI: 36.3 ± 0.7 kg/m, 2 ), energy intake (intake-balance method), and changes in weight, fasting glucose, insulin, lipids and habitual sleep (5 consecutive nights via wrist worn accelerometer) were assessed from early (13, 0 –15, 6 weeks) to late (35, 0 –36, 6 ) pregnancy. A change to habitual sleep parameters (increase or decrease) was defined as ± one-half of the standard deviation of the 5-day measurement in early pregnancy. Results: Results In early pregnancy, time spent in bed (TIB) was 9.40 ± 0.13 h and varied 1.61 ± 0.11 h across the 5 nights. Total sleep time (TST) and sleep efficiency (SE) significantly declined from early to late pregnancy 7.05 ± 0.13 h to 6.46 ± 0.15 h ( P  < 0.001) and 76 ± 0.1% to 71 ± 0.2% ( P  < 0.001), respectively. Women who increased TIB (11 of 52) had a significant decrease in plasma glucose −11.6 ± 4.3% ( P  < 0.01) and a trend towards lower insulin (−57.8 ± 33.5%; P  = 0.09) and HOMA-IR (−72.4 ± 37.3%; P  = 0.058) across pregnancy compared to women who decreased their TIB (13 of 52). Women who increased TIB had a significantly lower daily energy intake (−540 ± 163 kcal; P  < 0.01) and tended to have less gestational weight gain (−146.7 ± 87.6 g/wk; P  = 0.10). There was no difference in weight gain, energy intake or plasma markers between women who increased or decreased TST or SE. Conclusions: Although sleep time and sleep quality decline throughout pregnancy, TIB had the greatest impact on metabolic health in pregnant women with obesity. Women spending more TIB consumed fewer calories. Our data suggest that the relationship between glucose metabolism and sleep during pregnancy is at least in part explained by lower energy intakes, possibly due to shorter eating windows. Studies that manipulate the eating window, independent of sleep timing are needed to understand the benefits to metabolic health for women during pregnancy. Funding Sources: National Institutes of Health [R01DK099175].